Knowledge levels of obstetricians and gynecologists on deep vein thrombosis - Balcı, Abdullah Burak; Rahman, Ömer Faruk; Dağdeviren, Emrah (The European Research Journal, 2025)
Objectives: The aim of this study was to evaluate the level of knowledge of obstetricians and gynecologists about deep vein thrombosis (DVT) in pregnancy. Methods: A cross-sectional questionnaire comprising 12 items was administered to obstetricians and gynecologists employed at a tertiary care hospital between January 2024 and March 2024. Following a reliability analysis, a DVT questionnaire scale was developed, which was subsequently evaluated across three sub-dimensions: (1) General Disease Knowledge (F1), (2) Medical Treatment Knowledge (General) (F2), and (3) Anticoagulant Knowledge Level (F3). Results: A total of 163 participants were evaluated in the study, with a mean age of 32.33±5.75 years. Among these individuals, 107 (65.6%) were female and 56 (34.3%) were male. Additionally, 72 (44.2%) of the participants were classified as resident physicians. The scores for the sub-dimensions of the DVT scale were as follows: 2.25±1.03 for (F1), 1.33±0.72 for (F2), and 2.53±1.09 for (F3). Notably, (F3) of the resident physicians was found to be significantly lower than that of the specialist/faculty member group, with a P-value of less than 0.017. Conclusions: The study demonstrated that the knowledge levels of obstetricians and gynecologists fell below the established proficiency threshold. This deficiency is believed to stem from inadequate understanding of the differentiation between superficial and deep vein thrombosis, the management of anticoagulant therapy during pregnancy, and post-thrombotic syndrome. Enhancing awareness in these areas may improve patient outcomes, reduce reliance on cardiovascular surgery consultations, and alleviate clinical workload.